问题 解答题
计算:
(1)-72+72÷36                           
(2)3
2
3
×(
1
3
-
1
2
3
11
÷
5
4

(3)(-1)3-(1-
1
2
)÷3×[2-(-3)2]
(4)-92+2×(-3)2-(-6)÷(-
4
3
)

(5)-2×(-
1
2
)2+|-(-2)|3-(-
1
2
)

(6)(
1
50
-1)×(
1
49
-1)×(
1
48
-1)×…×(
1
4
-1)×(
1
3
-1)×(
1
2
-1)
答案

(1)-72+72÷36 

=-72+2

=-70;

                          

(2)3

2
3
×(
1
3
-
1
2
3
11
÷
5
4

=

11
3
×(-
1
6
)×
3
11
×
4
5

=

2
15

(3)(-1)3-(1-

1
2
)÷3×[2-(-3)2]

=-1-

1
2
×
1
3
×[2-9]

=-1-

1
6
×[-7]

=-1+

7
6

=

1
6

(4)-92+2×(-3)2-(-6)÷(-

4
3
)

=-81+2×9-4.5

=-81+18-4.5

=-67.5;

(5)-2×(-

1
2
)2+|-(-2)|3-(-
1
2
)

=-2×

1
4
+8+
1
2

=-

1
2
+8+
1
2

=8;

(6)(

1
50
-1)×(
1
49
-1)×(
1
48
-1)×…×(
1
4
-1)×(
1
3
-1)×(
1
2
-1)

=-

49
50
×
48
49
×…×
2
3
×
1
2

=-

1
50

单项选择题 A1/A2型题
名词解释